Comprehensive geological analysis and evaluation of the feasibility of renovating the Wanshunchang gas reservoir into a gas storage facility - Zebin Tong; Zhonggui Hu; Longwei Qiu; Na Zhang; Huayin Zhu; Daoyong Zhou; Gang Zhou; Xiao Chen; Yanlin Shao; Jiuzhen Hu (Scientific Reports, 2025)
Abstract As many oil and gas reservoirs approach depletion stages in the future, alongside growing energy storage demands, constructing gas storage facilities becomes critical for ensuring a stable natural gas supply. Consequently, a comprehensive geological analysis is essential to evaluate the feasibility of converting depleted gas reservoirs into gas storage facilities. The W gas reservoir in the Sichuan Basin, China, is nearing depletion and presents potential for conversion into a gas storage facility. This study provides a comprehensive geological evaluation to determine its feasibility for such conversion. Exploration and production data indicate that the W gas reservoir is a pore-fracture type carbonate reservoir. Vertically, the sub-layer beneath C2hl2 demonstrates the best physical properties. Horizontally, the area enclosed by wells C30, C10, and C18 exhibits favorable reservoir characteristics. The reservoir’s caprock comprises a superimposed composite system, including the direct caprock of the Liangshan Formation and an overlying ultra-thick dense rock layer, which is extensive and exhibits high breakthrough pressure. Nine major faults control the structural trap’s shape and scale. These faults, in a compressive state, are well-sealed due to fault gouge, enhancing their closure. The reservoir space is primarily pore-fracture type, and rapid injection and withdrawal induce minimal pressure changes, indicating low stress sensitivity. The comprehensive evaluation concludes that the Carboniferous gas reservoir possesses favorable geological conditions, making it suitable for conversion into a gas storage facility. This study offers a preliminary geological evaluation of the feasibility of converting fault-controlled fracture-type carbonate reservoirs into gas storage facilities and outlines directions for future research.